2007
DOI: 10.1152/ajpgi.00221.2006
|View full text |Cite
|
Sign up to set email alerts
|

Adequate oral threonine is critical for mucin production and gut function in neonatal piglets

Abstract: In previous experiments, we found that the threonine requirement of neonatal piglets fed parenterally was 40% of that when fed intragastrically; we hypothesized that much of the oral supply of threonine is being used for mucin production. To investigate this hypothesis, intragastrically fed 2-day-old piglets were fed one of three treatments for 8 days: 1) a threonine-adequate diet (IG-A; 0.6 g threonine.kg(-1).day(-1) fed intragastrically); 2) a threonine-deficient diet (IG-D; 0.1 g threonine.kg(-1).day(-1) fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 28 publications
4
89
0
3
Order By: Relevance
“…In the present study, the level of dietary threonine supply modified neither daily weight gain nor feed efficiency. This lack of effect of threonine deficiency on growth was also observed in early-weaned piglets fed a diet supplying only 17% of threonine requirements for a short period of time (Law et al, 2007). This result was quite unexpected since several studies showed that low dietary threonine supply decreases growth of weaning piglets (Sewell et al, 1953;Adeola et al, 1994) and growing pigs (Le Floc'h et al, 1994;Schutte et al, 1997).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In the present study, the level of dietary threonine supply modified neither daily weight gain nor feed efficiency. This lack of effect of threonine deficiency on growth was also observed in early-weaned piglets fed a diet supplying only 17% of threonine requirements for a short period of time (Law et al, 2007). This result was quite unexpected since several studies showed that low dietary threonine supply decreases growth of weaning piglets (Sewell et al, 1953;Adeola et al, 1994) and growing pigs (Le Floc'h et al, 1994;Schutte et al, 1997).…”
Section: Discussionmentioning
confidence: 86%
“…This can be related to the complexity in analysing mucin biology and characteristics. Total crude mucin content is reduced in the colon but not in the ileum of early-weaned piglets receiving 17% of threonine requirements for 1 week (Law et al, 2007). In adult rats fed 30% of threonine requirements for growth (Faure et al, 2005), mucins synthesis is impaired in the ileum and the colon.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations